(untitled) (Journal of Science and Technology, 2025)
Seed dormancy influences the regeneration of plants worldwide. Several methods have been reported to break seed dormancy in different plants, but we cannot generalise the methods because the dormancy types differ among and between species. Adansonia digitata L. (Baobab) seeds do not germinate readily under natural conditions. In baobabs, seed dormancy is caused by the hard seed coat (testa) and pulp. The tree is very useful apart from being deforested in many regions of the world. This study therefore aimed to explore the effectiveness of different seed pre-treatment methods on breaking seed dormancy in baobab. Specifically, the study intended to provide knowledge on the germination percentage of baobab seeds under different pre-treatment methods and resultant vigour of the seedlings. Experimentation involved Randomized Complete Block Design using six blocks with six treatments (hot water, cold water, smoke, acid, dry heat and water at room temperature). Standard methods were used to determine germination percentage, germination speed and seedling vigour of baobab under the aforementioned seed pre-treatment methods. The differences in germination percentage, germination speed and seedling vigour in all methods were significant (p < 0.05). The best methods for enhancing germination of baobab seeds and vigour of seedlings are hot water, acid (H2 SO4) and dry heat. On the other hand, the best methods for enhancing germination speed are cold water and the control. Therefore, we recommend the use of hot water and acid (sulfuric acid 98%) in preparation of nurseries for planting baobab seeds.